Race, Exclusionary Discipline, and Connectedness to Adults in Secondary Schools. Issue 3 (25th May 2016) - Anyon, Yolanda; Zhang, Duan; Hazel, Cynthia
Abstract: This study examines racial differences in students' connectedness to school adults and considers the possibility that disparities in exclusionary discipline practices may reduce all students' sense of connection to educators, not just those who have been disciplined or are from racial groups overrepresented in out‐of‐school suspensions. Data sources include a self‐report survey of secondary school students ( n  = 29, 148) linked to administrative data ( n  = 107 schools) from a large urban district. Multilevel modeling techniques were used to estimate the relationships between students' racial background, youths' connection to school adults, and school‐level racial discipline gaps. Controlling for school racial composition, gender, grade level and other covariates, students of color were significantly less likely to feel connected to school adults than their White peers. Additionally, the racial discipline gap was significantly and negatively associated with connectedness for all students. Results indicate that strategies to improve educational outcomes for youth of color need to attend to relational dynamics between students and school adults. Research findings also suggest that efforts to reduce discipline disparities may improve all students' connectedness.